PARTISIPASI PEREMPUAN DALAM PERENCANAAN PEMBANGUNAN DI TINGKAT DESA (STUDI KASUS DESA AMPELSARI KECAMATAN PETANAHAN KABUPATEN KEBUMEN) - Maria Christina Kusumaningtyas; Fitriyah Fitriyah (Journal of Politic and Government Studies, 2026)
Women's participation is key to inclusive development, but it is often hampered by patriarchal culture, limited access to decision-making, and domestic burdens. Interestingly, Ampelsari Village in Kebumen shows a different dynamic with a high level of women's involvement in the Musrenbangdes (Village Development Planning Forum). This is driven by the leadership of the female village head, who has opened up wider opportunities for participation. This phenomenon makes Ampelsari Village a highly relevant location for further study on how gender-responsive village development planning processes take place. This study aims to analyse the level of women's participation in village development planning through the Musrenbangdes forum and to identify the factors that influence this involvement. This study uses a qualitative approach with a case study method. Data collection was conducted through in-depth interviews and documentation. The research analysis uses several theoretical frameworks, namely political participation theory with Arnstein's ladder of participation approach, gender theory that explains the division of women's social roles, and participatory planning theory that emphasises the importance of community involvement in the development process. The results show that women's participation in Musrenbangdes in Ampelsari Village is not only evident from their formal attendance but also from their involvement in the process of expressing their aspirations and proposing development programmes. The attendance rate of women in the Musrenbangdes forum reached more than 38 per cent of the total participants. A number of proposals originating from women's groups, such as family health programmes, household economic empowerment, and the strengthening of women's organisations, have been accommodated in the Village Government Work Plan (RKPDes). This condition shows a shift in the form of women's participation from mere symbolic presence to more substantive participation in the development planning process. Overall, this study concludes that women's participation in development planning in Ampelsari Village has reached a higher level of participation, namely approaching the level of partnership. However, this participation still faces obstacles such as patriarchal culture, women's limited access to strategic positions in village institutions, and the burden of domestic roles that affect their level of involvement in public forums.